Long distance training associated to HIIT protocol does not induce changes in blood biochemical markers in adult marathoners - João Paulo Vieira Manechini; Rodrigo Aquino; Camila Moraes; Hugo Tourinho Filho; Pedro Mingoni Pimenta; Enrico Fuini Puggina (Colégio Brasileiro de Ciências do Esporte, 2020)
ABSTRACT Objective: to verify blood markers during a 12-week training protocol and after Sao Paulo Marathon. Methods: Blood samples of 9 male marathoners were collected before (C1) and after (C2) 12-week training protocol, before (C3) and after (C4) marathon. Muscle and liver damage markers (creatine kinase [CK-MM], aspartate aminotransferase [AST], alanine aminotransferase [ALT]), oxidative stress levels (thiobarbituric acid reactive substances [TBARS]) and serum iron concentration were measured. Results: changes were identified comparing moment C4 to other moments for CK-MM and iron. For AST, ALT, and TBARS no differences were identified. Conclusion: strenuous exercises might elicit changes on blood markers, needing follow up strategies to avoid impairments to athletes' performance and health.